Anaesthesia, Pain, Intensive Care and Emergency Medicine — A.P.I.C.E. Proceedings of the 15th Postgraduate Course in Critical Care Medicine Trieste, Italy — November 17–21, 2000 - Gullo, Antonino (Springer Milan, 2001)
The interest of researchers, clinicians, practitioners and surgeons in critical care medicine is growing. Clinical pharmacology and new technologies now allow more appropriate therapies, and the commitment of all those involved in this field is of fundamental importance for reaching high interventional standards, in both the prevention and treatment of critical conditions, but also for satisfying the concept of cost-effectiveness in critical care. In this volume advances in critical care medicine are described, including the application of new technologies in the clinical setting, the full integration of computers and informatics, and the continual training of physicians and technicians
Keywords: Anesthesiology; Intensive / Critical Care Medicine; Critical care medicine; Anästhesie; Schmerztherapie; Notfalltherapie; Intensivtherapie; Konferenzschrift -- 2000 -- Triest